An investigation of career decidedness in relation to "big five" personality constructs in adolescence / Muna Saif Abdullah Al-Kalbani - Abdullah Al-Kalbani, Muna Saif (2010)
The aims of the study were (І) to develop and test the psychometric properties of the Career Decision making indicators (CDMI), (П) to examine the psychometric properties of the Adolescent Personal Style Inventory (APSI), and (III) to find out the relationship between adolescent personality and career decidedness constructs. The participants constituted of 3260 students from the 10th, 11th and 12th grade, whom randomly were selected from the graduating class of 2008 in Sultanate of Oman. There are two instruments that were used in this study. The First is The Adolescent Personal Style Inventory (APSI) (Lounsbury,Tatum, Gibson, Park, Sundstrom & Hamrick, 2003). The Second is the Career Decision Making Indicators (CDMI). The APSI used to measure the five factors of personality (Neuroticism, Extroversion, Openness, Agreeableness, and Conscientiousness). As there was no Arabic version for the APSI yet available, The preliminary part of the research focus on the translation of this instrument into the Arabic language through a series of translation and back-translation processes. The results provide evidence that the adapted instrument achieved sound psychometric properties. The reliability test indicated that the instrument was reliable given the overall reliability value of Cronbach’s Alpha was .769. The findings revealed that with the use of EFA, The Adolescent Personal Style Inventory construct produced 5 significant factors. The CFA results showed that the goodness-of-fit indices for the revised model were as follows: χ2 (df = 179) = 387.903, CFI=.923; GFI= .965, PCOLOSE =1.00 and RMSEA=.034; each of the indices was above the threshold values. Two separate studies were conducted to develop the Career Decision Making Indicators (CDMI) and validate it. The CDMI measure the individual along eight dimensions: decidedness, comfort, Career Choice Anxiety, External Barrier, Need for Information, Readiness, Career Salience, and Inconsistent Information. The instrument has been devised and validated through a scientific method to ensure its reliability and validity. The results provide evidence that the developed instrument achieved sound psychometric properties. The overall reliability value of Cronbach’s Alpha was .935. Also by Using EFA, the Career Decision Making Indicators (CDMI) Inventory construct produced eight significant factors. The CFA results showed that the goodness-of-fit indices for the revised model were as follows: χ2 (df =712) =1802.559, CFI=.913; GFI= .927, PCOLOSE =1.00 and RMSEA=.036; each of the indices was above the threshold values. Analysis of the measurement invariance across samples confirmed the instrument’s factorial validity. Moreover, Big Five personality traits were analyzed in relation to career decidedness among adolescents. Neuroticism was found to be negatively related to career decidedness. While, Conscientiousness, Extroversion, Openness and Agreeableness constructs were positively and significantly correlated with career decidedness. Results are discussed in terms of implications for future research and career development efforts.